Halloysite-based intumescent flame-retardant early-warning impregnation liquid as well as preparation method and application thereof
By mixing the Elosite-based expanded flame retardant with graphene oxide and introducing delignin wood through vacuum impregnation and hot pressing treatment, the problem of wood flammability and long warning time for traditional early warning systems is solved, and efficient fire warning and flame retardant performance improvement is achieved.
Patent Information
- Application Number
- CN202510089558.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-04
AI Technical Summary
Wood is flammable and traditional fire smoke detectors have a long warning time and low sensitivity, making it difficult to meet the needs of wood for fire safety.
The Elosite-based expansion-type flame retardant early warning impregnation liquid is used. This liquid achieves efficient fire warning and flame retardant properties by mixing the Elosite-based expansion-type flame retardant with graphene oxide and introducing it into the delignin wood through vacuum impregnation and hot pressing treatment.
This method can achieve rapid fire response and long-term continuous early warning under flame conditions, improves the high temperature resistance and flame retardant performance of wood, can reach the V-0 level of vertical combustion test, and significantly improves the mechanical properties of wood.
Smart Images

Figure CN119748583A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame retardant materials and composite plates, and specifically relates to a halloysite-based intumescent flame retardant early warning impregnation liquid, a preparation method and an application thereof. Background Art
[0002] Wood is one of the most abundant, sustainable and beautiful structural materials, and is commonly used in fields such as furniture and construction. Unfortunately, the fire hazard of wood is a major safety issue in its practical application. Wood has inherent defects such as being flammable and releasing toxic fumes during combustion, and its direct use cannot meet the demand for wood in social development. The difficulties in fire safety of wood and wood products are mainly concentrated in the following two aspects: (1) Wood is flammable and the flame spreads rapidly when burning, which poses a high potential fire risk; (2) The warning time of traditional sensors such as fire smoke detectors is usually more than 100 seconds, and their sensitivity is low, resulting in a slow warning response. In addition, the rapid destruction and collapse of wooden buildings is another major cause of fire, which highlights the importance of combining flame retardancy and mechanical strength.
[0003] Compared with halogen flame retardants, intumescent flame retardants have the characteristics of high efficiency and low toxicity. Recently, they have been widely used in many fields and have become a hot spot for research and application of flame retardancy. There are two main ways to introduce flame retardants into wood and reduce the flammability of wood: the application of fire retardant coatings and the impregnation of flame retardants. Wood fire retardant coatings usually use compounds containing halogens, boron, phosphorus, nitrogen and inorganic metals (such as Al, Mg and Zn). Impregnation allows small-sized flame retardants to penetrate into the interior of the wood, ensuring a longer-lasting flame retardant efficiency. For example, organic phytic acid, inorganic calcium carbonate, nanomaterials, etc. can penetrate into the interior of the wood through impregnation to improve the flame retardancy of the wood. Although these flame retardants significantly improve the flame retardancy of wood, they also need to be used in conjunction with fire alarm devices to attract people's attention when a fire occurs.
[0004] Graphene oxide (GO), a two-dimensional (2D) layered nanomaterial consisting of a series of reactive graphene oxide flakes, has shown broad application prospects in a variety of fields, including nanoelectronics, biomedical applications, energy storage technology, and composite materials. GO is electrically insulating at room temperature, which is due to the fact that the C=O in its structure destroys the sp2 conjugated structure of the hexagonal graphene lattice. However, under high temperature or flame attack, oxygen-containing functional groups in its molecular structure, such as hydroxyl, carboxyl, ester, and water molecules, can be removed and the electrically insulating GO is rapidly converted into highly conductive reduced graphene oxide (RGO). However, due to its poor thermal stability in atmospheric conditions, RGO may be quickly and completely consumed during combustion. Therefore, fire warning sensors made solely of pure GO may not provide a sufficiently long fire alarm time. In general, GO-based fire alarm systems, as a surface coating, are limited in improving the flame retardancy of substrates, especially large-size bulk wood used in the construction field. Therefore, if the two methods of vacuum impregnation and hot pressing can be combined, it is expected to significantly improve the flame retardant properties and mechanical properties of wood and give it intelligent response functions. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a halloysite-based intumescent flame-retardant early warning impregnation liquid, a preparation method and an application thereof. The flame-retardant early warning impregnation liquid prepared by mixing a halloysite-based intumescent flame retardant with graphene oxide is introduced into delignified wood to exhibit efficient early warning behavior, and can simultaneously have rapid fire response under flame conditions and long-term continuous early warning functions.
[0006] The technical solution provided by the present invention is as follows:
[0007] The present invention provides a method for preparing a halloysite-based intumescent flame retardant early warning impregnation liquid, the method comprising the following steps: preparing melamine, adenosine triphosphate and halloysite nanotube aqueous solutions respectively; Dropping the halloysite nanotube aqueous solution into the melamine aqueous solution, heating under reflux and stirring to obtain a first mixed solution; Adding the adenosine triphosphate aqueous solution dropwise into the first mixed solution, heating under reflux and stirring to obtain a second mixed solution; The second mixed solution is cooled to room temperature and allowed to stand to obtain a precipitated product, and the precipitated product is then washed, filtered, dried and ground to obtain a pure and dry halloysite-based intumescent flame retardant powder; Halloysite-based intumescent flame retardant powder and graphene oxide powder are mixed and dispersed in deionized water to obtain the halloysite-based intumescent flame retardant early warning impregnation liquid.
[0008] Furthermore, the mass ratio of melamine, adenosine triphosphate and halloysite nanotubes is 1:2:1.
[0009] Furthermore, the halloysite nanotube aqueous solution or the adenosine triphosphate aqueous solution is controlled to be added dropwise within 20 to 40 minutes, and heated, stirred, refluxed and condensed at 80° C. for 1 to 3 hours.
[0010] Furthermore, the standing time is 8 to 10 hours, the precipitated product is washed and filtered multiple times with ultrapure water, and vacuum dried at 40 to 50° C. for 10 to 12 hours, and the dried precipitated product is ball-milled for 4 to 6 hours.
[0011] Furthermore, the mass of the halloysite-based intumescent flame retardant powder is 10-30wt% of the mass of the graphene oxide powder, and the halloysite-based intumescent flame retardant powder and the graphene oxide powder are dissolved in deionized water by ultrasonic dispersion to obtain a mixed solution.
[0012] The present invention also provides a halloysite-based intumescent flame-retardant early warning impregnation liquid, which is prepared according to the method described above.
[0013] The present invention also provides an application of the above-mentioned halloysite-based intumescent flame retardant warning impregnation liquid in the preparation of flame retardant warning wood. The preparation method of the flame retardant warning wood comprises the following steps: The wood is added into a delignification solution for pretreatment, and after the reaction is completed, the wood is washed with deionized water and freeze-dried to obtain delignified wood; The delignified wood is immersed in a flame retardant warning impregnation liquid, and vacuum impregnation treatment is performed under pressure to obtain vacuum impregnated wood; The vacuum impregnated wood is dried, and then the dried wood is hot pressed to obtain halloysite-based dense flame retardant warning wood after the hot pressing. Furthermore, the delignification solution is an alkaline delignification solution made of sodium hydroxide and sodium sulfite or an acidic delignification solution made of anhydrous sodium acetate and glacial acetic acid.
[0014] Furthermore, the conditions of the vacuum impregnation treatment include: controlling the vacuum degree to be 0.09-0.1 MPa, the pressure to be 4-5 MPa, and the vacuum impregnation time to be 6-9 hours.
[0015] Furthermore, the conditions of the hot pressing treatment include: controlling the hot pressing temperature to 90-100° C., the pressure to 5-7 MPa, and the hot pressing time to 4-5 h.
[0016] Beneficial Effects
[0017] 1. The flame retardant warning impregnation liquid prepared by mixing the halloysite-based intumescent flame retardant (MAH) with graphene oxide of the present invention exhibits efficient warning behavior after being introduced into delignified wood, and can simultaneously have rapid fire response under flame conditions and long-term continuous warning functions.
[0018] 2. The prepared densified flame retardant early warning wood exhibits excellent high temperature resistance and high flame retardancy. The data show that the limiting oxygen index can reach up to 44.2% and can reach the V-0 level in the vertical burning test.
[0019] 3. At the same time, the densified flame retardant warning wood after hot pressing has better mechanical properties than conventional flame retardant modified wood, which broadens the application scope of flame retardant warning wood in the fields of construction and furniture. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The present invention provides a reaction synthesis route of a halloysite-based intumescent flame retardant (MAH).
[0021] Figure 2 The present invention is a flowchart of a method for preparing flame retardant warning wood and a performance test thereof.
[0022] Figure 3 This is a test diagram of the flame retardant warning wood triggering an early warning according to an embodiment of the present invention.
[0023] Figure 4 This is a schematic diagram of a flame retardant warning wood triggering an early warning according to an embodiment of the present invention. DETAILED DESCRIPTION
[0024] The embodiment of the present invention provides a method for preparing a halloysite-based intumescent flame retardant early warning impregnation liquid, the method comprising the following steps: preparing melamine, adenosine triphosphate and halloysite nanotube aqueous solutions respectively; Dropping the halloysite nanotube aqueous solution into the melamine aqueous solution, heating under reflux and stirring to obtain a first mixed solution; Adding the adenosine triphosphate aqueous solution dropwise into the first mixed solution, heating under reflux and stirring to obtain a second mixed solution; The second mixed solution is cooled to room temperature and allowed to stand to obtain a precipitated product, and the precipitated product is then washed, filtered, dried and ground to obtain a pure and dry halloysite-based intumescent flame retardant powder; Halloysite-based intumescent flame retardant powder and graphene oxide powder are mixed and dispersed in deionized water to obtain the halloysite-based intumescent flame retardant early warning impregnation liquid.
[0025] In this embodiment, the mass ratio of melamine, adenosine triphosphate and halloysite nanotubes is 1:2:1.
[0026] In this embodiment, the halloysite nanotube aqueous solution or the adenosine triphosphate aqueous solution is controlled to be added dropwise within 20-40 minutes, and heated, stirred, refluxed and condensed for 1-3 hours at 80°C.
[0027] In this embodiment, the standing time is 8 to 10 hours, the precipitated product is washed and filtered multiple times with ultrapure water, and vacuum dried at 40 to 50° C. for 10 to 12 hours, and the dried precipitated product is ball-milled for 4 to 6 hours.
[0028] In this embodiment, the mass of the halloysite-based intumescent flame retardant powder is 10-30wt% of the mass of the graphene oxide powder, and the halloysite-based intumescent flame retardant powder and the graphene oxide powder are dissolved in deionized water by ultrasonic dispersion to obtain a mixed solution.
[0029] The embodiment of the present invention also provides a halloysite-based intumescent flame retardant early warning impregnation liquid, which is prepared according to the method described above.
[0030] The embodiment of the present invention also provides a use of the above-mentioned halloysite-based intumescent flame retardant warning impregnation liquid in the preparation of flame retardant warning wood, and the preparation method of the flame retardant warning wood comprises the following steps: The wood is added into a delignification solution for pretreatment, and after the reaction is completed, the wood is washed with deionized water and freeze-dried to obtain delignified wood; The delignified wood is immersed in a flame retardant warning impregnation liquid, and vacuum impregnation treatment is performed under pressure to obtain vacuum impregnated wood; The vacuum impregnated wood is dried, and then the dried wood is hot pressed to obtain halloysite-based dense flame retardant warning wood after the hot pressing. In this embodiment, the delignification solution is an alkaline delignification solution made of sodium hydroxide and sodium sulfite or an acidic delignification solution made of anhydrous sodium acetate and glacial acetic acid.
[0031] In this embodiment, the conditions of the vacuum impregnation treatment include: controlling the vacuum degree to be 0.09-0.1 MPa, the pressure to be 4-5 MPa, and the vacuum impregnation time to be 6-9 hours.
[0032] In this embodiment, the conditions of the hot pressing treatment include: controlling the hot pressing temperature to 90-100° C., the pressure to 5-7 MPa, and the hot pressing time to 4-5 h.
[0033] The following is a detailed description of a halloysite-based intumescent flame retardant early warning impregnation liquid, a preparation method and an application thereof provided by the present invention in conjunction with the embodiments (combined with Figure 1-Figure 4 and Table 1), but they should not be construed as limiting the scope of protection of the present invention.
[0034] The testing methods for the performance indicators involved in the following embodiments and comparative examples are as follows:
[0035] (1) Limiting oxygen index test (LOI): The wood samples were tested using an oxygen index meter (JF-3, Nanjing Jiangning District Analytical Instrument Factory) in accordance with GB / T 2406.2-2009 "Test method for combustion performance of plastics - oxygen index method".
[0036] (2) Vertical burning test (UL-94): The wood specimens are tested in accordance with GB / T 2408-2008 "Determination of burning performance of plastics - Horizontal and vertical methods". V-0 and V-1 are V-level fire test grades, where V-0 is better than V-1, and NR means that the test failed.
[0037] (3) Fire warning test (FWT): The test is conducted using a laboratory-made fire warning device, which mainly consists of an adjustable low-voltage power supply (20.0 V), a warning light, an alcohol lamp, and several wires.
[0038] (4) Bending performance test: A universal mechanical testing machine (INSTRON, 5966B11400) was used to conduct three-point bending performance tests on natural wood and densified wood to test their bending strength and bending modulus. The speed was set to 5 mm / min, with 6 repetitions per group. The specimen size was 100 mm×10 mm×5 mm.
[0039] Example 1
[0040] A halloysite-based intumescent flame retardant early warning impregnation liquid, a preparation method and an application thereof, the specific steps are as follows:
[0041] (1) Weigh 1.0 g of halloysite nanotubes (HNTs) and dissolve them in 80 mL of deionized water. Place the HNTs in a 250 mL three-necked flask and heat to 80 °C at 600 r / min. -1 1.0 g of melamine (Mel) was weighed and dispersed in 30 mL of deionized water, and then ultrasonically treated at room temperature for 20 min. Then, the mixture was slowly added to the three-necked flask using a dropping funnel within 40 min, and the reaction was maintained at 80 °C for 1 h under reflux.
[0042] (2) Weigh 2.0 g of adenosine triphosphate (ATP) powder and dissolve it in 30 mL of deionized water. Stir at room temperature for 30 min to obtain ATP solution. Use a dropping funnel to drop the prepared ATP solution into a three-necked flask drop by drop over 40 min. After the addition is complete, stir the mixed solution magnetically at 80 °C for 3 h to allow it to react fully.
[0043] (3) After the reaction is completed, the mixture is allowed to stand at room temperature for 10 hours to obtain a precipitated product. The precipitated product is washed with ultrapure water for multiple times to remove surface impurities and filtered. The washed precipitate is collected in a glass culture dish, sealed with a sealing film and pores are left on the surface of the sealing film. The dish is placed under vacuum drying at 40°C for 12 hours to obtain pure and dry halloysite-based intumescent flame retardant MAH powder.
[0044] (4) 0.25 g of flame retardant MAH powder and 1.25 g of graphene oxide (GO) powder were mixed in 500 mL of deionized water solvent and heated at 600 r·min. -1 The mixture was magnetically stirred at a stirring speed of 100 for 12 hours to fully dissolve, thereby obtaining a flame retardant warning impregnation solution.
[0045] (5) The above-mentioned flame retardant warning impregnation liquid is applied to wood flame retardant warning. Specifically, the wood is sawn into 20mm×10mm×10mm wood samples, and the wood samples are subjected to acid delignification (CH 3 COONa / NaClO 2 ), specifically: weigh 54g of anhydrous sodium acetate and dissolve it in 500mL of deionized water, stir until completely dissolved, use a dropper to titrate glacial acetic acid to a pH of 4.6, and then add 500mL of deionized water to dilute the solution to 1000mL. Heat the wood sample in an oil bath in the prepared acidic solution at a heating temperature of 100°C for 9 hours. After delignification, rinse the wood sample with deionized water and freeze-dry for 3 days.
[0046] (6) The flame retardant warning impregnation liquid prepared by GO and MAH was impregnated into the delignified wood using a vacuum impregnation tank and repeatedly pressed for 6 hours. The dried wood was then hot pressed for about 5 hours at a pressure of 4.5 MPa and a temperature of 100°C, and the thickness of the wood sample was compressed from 10 mm to 5 mm, achieving a compression rate of 50%.
[0047] Example 2
[0048] The embodiment of the present invention provides a halloysite-based intumescent flame retardant early warning impregnation liquid, a preparation method and an application thereof, and the specific steps are as follows:
[0049] (1) Weigh 1.0 g of halloysite nanotubes (HNTs) and dissolve them in 80 mL of deionized water. Place the HNTs in a 250 mL three-necked flask and heat to 80 °C at 600 r / min. -11.0 g of melamine (Mel) was weighed and dispersed in 30 mL of deionized water, and then ultrasonically treated at room temperature for 20 min. Then, the mixture was slowly added to the three-necked flask using a dropping funnel within 40 min, and the reaction was maintained at 80 °C for 1 h under reflux.
[0050] (2) Weigh 2.0 g of adenosine triphosphate (ATP) powder and dissolve it in 30 mL of deionized water. Stir at room temperature for 30 min to obtain ATP solution. Use a dropping funnel to drop the prepared ATP solution into a three-necked flask drop by drop over 40 min. After the addition is complete, stir the mixed solution magnetically at 80 °C for 3 h to allow it to react fully.
[0051] (3) After the reaction is completed, the mixture is allowed to stand at room temperature for 10 hours to obtain a precipitated product. The precipitated product is washed with ultrapure water for multiple times to remove surface impurities and filtered. The washed precipitate is collected in a glass culture dish, sealed with a sealing film and pores are left on the surface of the sealing film. The dish is placed under vacuum drying at 40°C for 12 hours to obtain pure and dry halloysite-based intumescent flame retardant MAH powder.
[0052] (4) 0.25 g of flame retardant MAH powder and 1.25 g of graphene oxide (GO) powder were mixed in 500 mL of deionized water solvent and heated at 600 r·min. -1 The mixture was magnetically stirred at a stirring speed of 100 for 12 hours to fully dissolve, thereby obtaining a flame retardant warning impregnation solution.
[0053] (5) The above-mentioned flame retardant warning impregnation liquid is applied to wood flame retardant warning. Specifically, the wood is sawn into 20mm×10mm×10mm wood samples, and the wood samples are subjected to alkaline delignification (NaOH / Na 2 SO 3 ), specifically: weigh 100g of sodium hydroxide and 50.4g of sodium sulfite and dissolve them in 1000mL of deionized water, stirring until completely dissolved. Heat the wood sample in an oil bath in the prepared alkaline solution at a heating temperature of 100°C for 9 hours. After delignification, rinse the wood sample with deionized water and freeze-dry for 3 days.
[0054] (6) The flame retardant warning impregnation liquid prepared by GO and MAH was impregnated into the delignified wood using a vacuum impregnation tank and repeatedly pressed for 6 hours. The dried wood was then hot pressed for about 5 hours at a pressure of 4.5 MPa and a temperature of 100°C, and the thickness of the wood sample was compressed from 10 mm to 5 mm, achieving a compression rate of 50%.
[0055] Comparative Example 1
[0056] Untreated wood, specifically: the wood was sawn into wood samples of 20 mm × 10 mm × 10 mm, the surface of the wood samples was sanded, and then cleaned with deionized water, and placed in an 80° C. oven to dry for 12 hours.
[0057] Comparative Example 2
[0058] The wood was sawn into wood samples of 20mm×10mm×10mm, and the wood samples were subjected to acid delignification. Specifically, 54g of anhydrous sodium acetate was weighed and dissolved in 500mL of deionized water, stirred until completely dissolved, glacial acetic acid was titrated with a dropper to a pH of 4.6, and then 500mL of deionized water was added to dilute the solution to 1000mL. The wood samples were heated in an oil bath in the prepared acidic solution at a heating temperature of 100°C for 9 hours. After delignification, the wood samples were rinsed with deionized water and freeze-dried for 3 days.
[0059] Comparative Example 3
[0060] The wood was sawn into wood samples of 20 mm × 10 mm × 10 mm, and the wood samples were subjected to alkaline delignification. Specifically, 100 g of anhydrous sodium acetate and 50.4 g of sodium sulfite were weighed and dissolved in 1000 mL of deionized water, and stirred until completely dissolved. The wood samples were heated in an oil bath in the prepared alkaline solution at a heating temperature of 100 ° C for 9 hours. After delignification, the wood samples were rinsed with deionized water and freeze-dried for 3 days.
[0061] Comparative Example 4
[0062] The embodiment of the present invention provides a method for preparing a graphene oxide impregnation solution and application thereof, and the specific steps are as follows:
[0063] (1) 1.25 g of graphene oxide (GO) powder was mixed with 500 mL of deionized water and heated at 600 r·min. -1 The mixture was stirred magnetically for 12 h at a stirring speed of 100 to fully dissolve to obtain an impregnation solution.
[0064] A method for preparing flame retardant early warning wood, the specific steps are as follows:
[0065] (2) The above impregnation liquid is applied to wood flame retardant early warning. Specifically, the wood is sawn into 20mm×10mm×10mm wood samples, and the wood samples are subjected to acid delignification (CH 3 COONa / NaClO 2), specifically: weigh 54g of anhydrous sodium acetate and dissolve it in 500mL of deionized water, stir until completely dissolved, use a dropper to titrate glacial acetic acid to a pH of 4.6, and then add 500mL of deionized water to dilute the solution to 1000mL. Heat the wood sample in an oil bath in the prepared acidic solution at a heating temperature of 100°C for 9 hours. After delignification, rinse the wood sample with deionized water and freeze-dry for 3 days.
[0066] (3) The GO impregnation solution was impregnated into the delignified wood using a vacuum impregnation tank and repeatedly pressed for 6 hours. The dried wood was then hot pressed for about 5 hours at a pressure of 4.5 MPa and a temperature of 100°C, reducing the thickness of the wood sample from 10 mm to 5 mm, achieving a compression rate of 50%.
[0067] Comparative Example 5
[0068] The embodiment of the present invention provides a method for preparing a graphene oxide impregnation solution, and the specific steps are as follows:
[0069] (1) 1.25 g of graphene oxide (GO) powder was mixed with 500 mL of deionized water and heated at 600 r·min. -1 The mixture was stirred magnetically for 12 h at a stirring speed of 100 to fully dissolve to obtain an impregnation solution.
[0070] (2) The above impregnation liquid is applied to wood flame retardant early warning. Specifically, the wood is sawn into 20mm×10mm×10mm wood samples, and the wood samples are subjected to alkaline delignification (NaOH / Na 2 SO 3 ), specifically: weigh 100g of anhydrous sodium acetate and 50.4g of sodium sulfite and dissolve them in 1000mL of deionized water, stirring until completely dissolved. Heat the wood sample in an oil bath in the prepared alkaline solution at a heating temperature of 100°C for 9 hours. After delignification, rinse the wood sample with deionized water and freeze-dry for 3 days.
[0071] (3) The GO impregnation solution was impregnated into the delignified wood using a vacuum impregnation tank and repeatedly pressed for 6 hours. The dried wood was then hot pressed for about 5 hours at a pressure of 4.5 MPa and a temperature of 100°C, reducing the thickness of the wood sample from 10 mm to 5 mm, achieving a compression rate of 50%.
[0072] The flame retardancy, early warning and mechanical properties of the embodiments and comparative examples were tested, and the test data are shown in Table 1:
[0073] Table 1 Flame retardant warning performance test data table
[0074]
[0075] As can be seen from Table 1, the wood samples of pure wood in Comparative Example 1, acid delignified wood in Comparative Example 2, and alkaline delignified wood in Comparative Example 3 are easy to burn and degrade when exposed to fire, and the fire warning function cannot be realized. The wood samples (Comparative Examples 4 and 5) impregnated with 2.5 mg / ml GO solution and hot pressed can trigger a fire alarm signal after being exposed to the flame for about 4-5 seconds, realizing agile and rapid early fire warning. The time for triggering the warning in Examples 1 and 2 exposed to the flame was 8.2 seconds and 9.0 seconds, respectively. This is because under the attack of fire, the GO attached to the surface of the wood can be rapidly carbonized at high temperature, and its current increases rapidly in a very short time. The insulating GO sheet is reduced at high temperature, and then the surface insulating layer is quickly converted into a conductive state, thereby realizing the early warning behavior of the fire.
[0076] Based on Comparative Examples 1 and 2 and 3, the limiting oxygen index (LOI) of the delignified wood samples increased from 23.1% to 29% and 32.5%, but all three failed the vertical combustion (UL-94) test. The limiting oxygen index of the wood samples (Comparative Examples 4 and 5) impregnated with 2.5 mg / ml GO solution and hot pressed was increased to 33% and 35.3%, and the continuous fire warning time was 57 and 65 minutes, respectively. This is mainly because the delignification treatment reduces the combustibles in the wood, and the densification process eliminates the space between the cell walls, thereby forming a high-density laminated structure that can organize oxygen entry. In addition, the insulating charcoal layer formed during the combustion process hinders the transfer of heat and the diffusion of oxygen. These synergistic effects help the material have excellent flame retardant and self-extinguishing properties. With the addition of halloysite-based intumescent flame retardant (MAH), the limiting oxygen index of the wood sample is greatly increased compared with that of comparative example 1, and is increased to 43.7% and 44.2%, which can reach the V-0 level of the vertical combustion test. As the flame continues to burn, Examples 1 and 2 can provide a continuous fire warning for more than 60 minutes, and the fire resistance of the surface wood sample is further enhanced with the addition of MAH in the impregnation liquid.
[0077] As can be seen from Table 1, the bending strength of the wood samples of Comparative Examples 2 and 3 decreased after delignification treatment, from the bending strength of the wood sample of Comparative Example 1 of 61.59 MPa to 56.16 MPa and 35.56 MPa respectively. The original stable chemical structure of the wood fiber is destroyed after the removal of lignin and hemicellulose, and the fiber bundles become loose, resulting in a decrease in the mechanical properties of the wood, but this problem can be overcome by physical hot pressing. The bending strength of the wood samples of Comparative Examples 4, 5 and Examples 1 and 2 increased to 192.37 MPa, 164.77 MPa, 227.28 MPa and 208.03 MPa respectively, of which the highest was the maximum bending strength of the wood sample of Example 1 of 227.28 MPa, which was 268% higher than that of the untreated wood sample. On the one hand, after delignification, wood still maintains a porous structure, and the porosity and wettability are significantly improved, so that the small molecules in the impregnation solution can be fully filled in it; on the other hand, this is because a large number of hydroxyl groups are exposed after wood delignification. Densification treatment through mechanical compression can make the wood fibers more tightly combined and strengthen the hydrogen bond connection between fibers. Therefore, in addition to good flame retardancy, densified wood also has excellent bending strength, which can effectively prevent the collapse and destruction of wooden structures.
[0078] From the above examples, it can be seen that the flame retardant warning impregnation liquid obtained by mixing halloysite-based intumescent flame retardant (MAH) with graphene oxide (GO) is introduced into delignified wood by a method combining vacuum impregnation and hot pressing. The densified flame retardant warning wood can form a closed circuit when in contact with a fire source, realize early fire warning, and at the same time, the flame retardant performance is gradually improved. The wood sample of the present invention can trigger a warning signal after contacting the fire source for 9.0 seconds and can maintain a warning time of up to 73 minutes. It has the characteristics of sensitive fire response, strong fire resistance, and excellent mechanical properties. It has important potential utilization value in actual fire prevention and protection, and at the same time broadens its use as a structural material in the fields of construction, furniture, etc.
[0079] The above is only a preferred embodiment of the present invention, and is not intended to limit the implementation methods. It should be noted that, for ordinary technicians in the relevant field, some improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the protection scope of the present invention.
Claims
1. A method for preparing a halloysite-based intumescent flame retardant early warning impregnation liquid, characterized in that: The method comprises the following steps: preparing aqueous solutions of melamine, adenosine triphosphate and halloysite nanotubes respectively; Dropping the halloysite nanotube aqueous solution into the melamine aqueous solution, heating under reflux and stirring to obtain a first mixed solution; Adding the adenosine triphosphate aqueous solution dropwise into the first mixed solution, heating under reflux and stirring to obtain a second mixed solution; The second mixed solution is cooled to room temperature and allowed to stand to obtain a precipitated product, and the precipitated product is then washed, filtered, dried and ground to obtain a pure and dry halloysite-based intumescent flame retardant powder; Halloysite-based intumescent flame retardant powder and graphene oxide powder are mixed and dispersed in deionized water to obtain the flame retardant warning impregnation liquid.
2. The method for preparing the halloysite-based intumescent flame retardant early warning impregnation liquid according to claim 1, characterized in that: The mass ratio of melamine, adenosine triphosphate and halloysite nanotubes is 1:2:
1.
3. The method for preparing the halloysite-based intumescent flame retardant early warning impregnation liquid according to claim 1, characterized in that: The halloysite nanotube aqueous solution or the adenosine triphosphate aqueous solution is controlled to be added dropwise within 20 to 40 minutes, and heated, stirred, refluxed and condensed for a reaction of 1 to 3 hours at 80°C.
4. The method for preparing the halloysite-based intumescent flame retardant early warning impregnation liquid according to claim 1, characterized in that: The standing time is 8 to 10 hours, the precipitated product is washed and filtered multiple times with ultrapure water, and vacuum dried at 40 to 50° C. for 10 to 12 hours, and the dried precipitated product is ball-milled for 4 to 6 hours.
5. The method for preparing the halloysite-based intumescent flame retardant early warning impregnation liquid according to claim 1, characterized in that: The mass of the halloysite-based intumescent flame retardant powder is 10-30wt% of the mass of the graphene oxide powder. The halloysite-based intumescent flame retardant powder and the graphene oxide powder are dissolved in deionized water by ultrasonic dispersion to obtain a mixed solution.
6. A halloysite-based intumescent flame retardant early warning impregnation liquid, characterized in that: Prepared according to the method according to any one of claims 1 to 5.
7. Use of the halloysite-based intumescent flame retardant warning impregnation liquid according to claim 6 in the preparation of flame retardant warning wood, characterized in that: The preparation method of the flame retardant early warning wood comprises the following steps: The wood is added into a delignification solution for pretreatment, and after the reaction is completed, the wood is washed with deionized water and freeze-dried to obtain delignified wood; The delignified wood is immersed in a flame retardant warning impregnation liquid, and vacuum impregnation treatment is performed under pressure to obtain vacuum impregnated wood; The vacuum impregnated wood is dried, and then the dried wood is hot pressed to obtain the halloysite-based dense flame retardant warning wood.
8. The use according to claim 7, characterized in that: The delignification solution is an alkaline delignification solution made of sodium hydroxide and sodium sulfite or an acidic delignification solution made of anhydrous sodium acetate and glacial acetic acid.
9. The use according to claim 7, characterized in that: The conditions of the vacuum impregnation treatment include: controlling the vacuum degree to be 0.09-0.1 MPa, the pressure to be 4-5 MPa, and the vacuum impregnation time to be 6-9 hours.
10. The use according to claim 7, characterized in that: The conditions of the hot pressing treatment include: controlling the hot pressing temperature to 90-100° C., the pressure to 5-7 MPa, and the hot pressing time to 4-5 hours.
Citation Information
Cited By
Anticorrosive flame-retardant coating and preparation method thereof
CN121930731A